Preharvest identification of bitter pit risk in 'Gala' apples by fruit infiltration with magnesium and analysis of fruit contents of calcium and nitrogen Identificação pré-colheita do risco de ocorrência de "bitter pit" em maçãs 'Gala' por meio de infiltração com magnésio e análise dos teores de cálcio e nitrogênio nos frutos - do Amarante C.V.T.* (2010)
Bitter pit is a postharvest physiological disorder in apples, related to Ca deficiency, and aggravated by high levels of Mg, N, and K in the fruits. This work was carried out to assess the practical viability of 'Gala' apples infiltration with Mg, for preharvest identification of bitter pit risk during cold storage, as well as, to identify the mineral attributes associated with the occurrence of the disorder. Fruits were sampled in 50 plots of apple orchards located in Fraiburgo, SC (Southern of Brazil). Samples of 25 fruits / plot were harvested about 20 days before commercial harvesting, and then vacuum infiltrated with Mg and assessed for incidence (%) and severity (pits / fruit) of bitter pit. Samples of 120 fruits were harvested in the same plots, at the commercial maturity. One hundred fruits were stored in conventional cold storage for four months (0° 0.5°C and 90-95% RH) and 20 fruits were analyzed for mineral content (Ca, Mg, K, and N). Cold stored fruit were assessed for incidence (%) and severity (pits / fruit) of bitter pit five days after removal from storage. There was a highly significant linear correlation (r2 = 0.69; p<0.001) between the incidence of bitter pit assessed in fruits infiltrated with Mg and in fruits left in cold storage. In both, fruits infiltrated with Mg and fruits left in cold storage, there was a decrease in Ca and an increase in N contents with increases of incidence and severity of bitter pit. Results show that preharvest infiltration of 'Gala' apples with Mg is a viable method to identified plots in a commercial orchard with risk to manifest bitter pit during cold storage.